Influence of Intellectual Capital Practices in Achieving Corporate Performance: Special Reference to Business Sectors in Colombo Stock Exchange - Larojan, C.; Janaki, S.T. (University of Jaffna, 2012)
The aim of this research paper is to investigate the influence of Intellectual Capital practices in achieving Corporate Performance in business sectors in Colombo Stock Exchange (CSE). This is an exploratory study based on analysing secondary data to examine the extent to which the 100 listed companies in 20 business sectors are adopting methodologies for reporting intellectual capital in their annual reports as of March 31, 2011. The Value Added Intellectual Coefficient (VAIC) has been employed to measure the Intellectual Capital together with the measurements of value creation efficiencies of capital employed, physical capital, human capital, and structural capital of selected firms. The authors construct Ordinary Least Square method of regression model to examine the relationship between influences of Intellectual Capital in achieving Corporate Performance. The results indicate that significant differences in market and book values of the 100 listed companies were found. Levels of voluntary disclosure of Intellectual Capital items are relatively low while disclosures are dominated by customer relations items. The results support the hypothesis that firms’ Intellectual Capital has a positive impact on market value and Corporate Performance, and may be an indicator for future Corporate Performance. In addition, the authors found investors may place different value on the three components of value creation efficiency (physical capital, human capital, and structural capital). The analysis indicates that influence of Intellectual capital practices on corporate performance are mixed, and findings suggest that human capital is very efficient than physical capital and structural capital. The results suggest the need for further developments in Sri Lanka Accounting Standards (LKAS) to take into account Intellectual Capital disclosure in annual reports of companies. This paper makes an original contribution to the growing body of empirical studies on Intellectual Capital reporting in Sri Lanka and describes the usefulness of Intellectual Capital reporting in Sri Lanka. The results of the study provide directions towards building a strong knowledge base for future Intellectual Capital development.
Keywords: Corporate Performance., Colombo Stock Exchange (CSE).; Intellectual Capital.; Sri Lanka Accounting Standard (LKAS).